Fenomenologia dell’esistenza nomade. Una linea di fuga deleuzeana - Capodivacca, Silvia (Scenari, 2024)
The article delves into the relationship between space and the formation of social groups, with a special focus on nomadic populations. It examines these societies, which are often misunderstood or undervalued by their sedentary counterparts. In doing so, it challenges widespread prejudices and uncovers the intricate cultural dynamics and preferences of nomads. The text dives deep into the ‘nomadic magma,’ highlighting the nomads’ resistance to a simplistic, linear understanding of human history. Additionally, the article seeks to explore the importance of space in defining a social conglomerate. It questions the prevailing belief that time is more crucial than space in identifying a discernible human collective. This leads to a pivotal inquiry: How do our interactions with the space around us shape the formation of social groups? Specifically, how does our environment and our relationship with it define our lifestyle? This perspective not only sheds light on everyday practices but also reveals the deep cultural, social, and philosophical connotations associated with a nomadic way of life. The methodological foundation of the research is grounded in the “Treatise on Nomadology” from Deleuze & Guattari’s A Thousand Plateaus. This is not only implicitly referenced throughout the study but is also directly engaged with in an effort to unravel the characteristics of the ‘nomad science’.